Organizational Communication - Porterfield, George Donald (Academy of Management Review, 1976)
This article presents reviews of several books including, ?Communication & Organizational Behavior: Text & Cases,? 3rd ed., by William V. Haney, ?Communication & Communication Systems in Organization, Management & Interpersonal Relations,? by Lee Thayer and ?Communication in Organizations, A Guide to Information Sources,? by Robert M. Carter.